Association Between Diabetes Medications and the Risk of Parkinson's Disease: A Systematic Review and Meta-Analysis - Qin, Xiaocui; Zhang, Xia; Li, Pinyu; Wang, Min; Yan, Li; Bao, Zeqing; Liu, Qili (Frontiers in Neurology, 2021)
Background: Diabetes mellitus (DM) increases the risk of Parkinson’s disease (PD). However, whether DM medications play a part on that increased PD risk is unclear. We designed this meta-analysis to assess the influence of different oral DM medications on the PD risk in patients with DM. Methods: We searched PubMed, Embase, and CENTRAL databases for relevant studies up until January 2021. We pooled adjusted outcomes to assess the PD risk in patients using different DM medications including sulfonylurea, metformin, glitazones (GTZ), dipeptidyl peptidase-4 inhibitors (DPP4i), and glucagon-like peptide-1 agonists (GLP1a). Results: We included 10 studies in our analysis. Our results indicate a lack of significant association between the PD risk and the use of sulfonylureas (3 studies; HR, 1.26; 95% CI, 0.95 to 1.66; I2,70%; p=0.11), DPP4i (3 studies; HR, 0.69; 95% CI, 0.35 to 1.38; I2, 88%; p=0.30), metformin (5 studies; HR, 1.23; 95% CI, 0.98 to 1.78; I2, 84%; p=0.13), and GTZ (6 studies; HR, 0.88; 95% CI, 0.66 to 1.16; I2, 92%; p=0.35). After exclusion of a single study in the GTZ analysis, our results indicate a significantly reduced PD risk with GTZ use (HR, 0.78; 95% CI, 0.65 to 0.93; I2, 59%; p=0.06). Similarly, after the exclusion of a single study, our results indicate a significantly increased PD risk with the use of metformin (HR, 1.50; 95% CI, 1.11 to 2.02; I2, 80%; p=0.008). We also found a significantly reduced PD risk with the use of GLP1a (2 studies; HR, 0.41; 95% CI, 0.19 to 0.87; I2, 0%; p=0.02). Conclusion: The role of different DM medications on the PD risk remains unclear and the quality of studies is low. While our analysis suggests a lack of association between the use of metformin, GTZ, DPP4i, and sulfonylureas and the PD risk, metformin (to a higher degree) and GTZ may still increase the risk. Limited data suggest a protective effect of GLP1a on the PD risk.